Tafsir Surah Al Fatihah (Telaah atas Pesan-Pesan al-Qur’an: Moncoba Mengerti Intisari Kitab Suci Karya Djohan Effendi) - Rohmah, Umi Nuriyatur (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2018)
Surah al-Fa>tihah is the opening surah of the Koran that contains the essencial knowledge of the entire surah in Koran. Learning the content of surah al-Fa>tihah means learning the whole Koran too. This article discusses about Djohan Effendi’s interpretation about Surah al-Fa>tihah: Research on book Pesan-pesan al-Qur’an: Mencoba Mengerti Intisari Kitab Suci. The core theme of this article is reveal Effendi’s interpretation about Surah al-Fa>tihah. The approach used in this article is analitical description (deskriptif analitis), it means to describe about Djohan Effendi’s interpretation about Surah al-Fa>tihah sistematically, objectively, and analitically. The result of this article is there are 4 (four) words those must be understood correctly, those are: Rabb, Rahma>n, Rahi>m, and Ma>lik. These words explain the position of Allah as the God of universe (Rabb al-‘A<lami>n), the God who create and keep it, explaining His relaition with human as manifestation of His Rahma>niyyah and Ra>hi>miyyah, His unconditional love and mercies, realize human that they will be responsible their doing in front of Ma>lik Yaum al-Di>n, the King of Judgement Day.